Conservatism and Innovation in Venture Capital Contracting. (8th July 2014) - McCahery, Joseph A.; Vermeulen, Erik P.M.
Abstract We conjecture that venture capitalists and their investors often fall prey to what is known as 'collective conservatism'. We investigate this conjecture by analysing boilerplate provisions in limited partnership agreements. When investors accept suboptimal boilerplate provisions it is not because they believe that the standardised terms and conditions sufficiently align the interests of investors and fund managers, but merely because they think their peers, including their competitors, prefer to include them in the limited partnership agreement. We find that the financial crisis has facilitated some notable deviations in the boilerplate provisions that are designed to facilitate the return of confidence in the venture capital industry. We argue that a gradual shift may be taking place towards more investor-favourable limited partnership agreements or separate account and pledge fund arrangements. These shifts — which do not lead to significant changes in limited partnership agreements — appear to be particularly effective for bigger funds that increasingly focus on later-stage investments. We show that early-stage funds are more inclined to enter into innovative collaborative agreements. Collaborative agreements differ from traditional limited partnership agreements in that they focus less on curtailing principal-agent problems and more on joint development and value creation.